(untitled) (International Journal of Medical and Surgical Sciences, 2015)
The anatomy applied to health sciences, and especially to surgical practice, in any of its branches, is fundamental for a correct approach to the affected area and a better resolution of the pathology. We present in this case report the case of a patient, a professional writer, with weakness in his right hand due to the subsequent discovery of anconeous epitrochlearis muscle. The case study describes the anatomical variation found and its subsequent resolution, stressing the need to keep in mind a possible morphological variation, to achieve an adequate clinical diagnosis and subsequent surgical correction.